Shedding light on sound: the fusion of acousto-optic and B-mode ultrasound imaging - Roy, R; Sui, L; Dimarzio, C; Murray, T (IEEE, 2006)
Ultrasound modulation of light can be used to image optical properties in highly diffusive media such as biological tissues. Much of the previous work in this area employed continuous wave (cw) ultrasound to pump the acousto-optic response. We argue in favor of using pulsed ultrasound, based on regulatory considerations related to bioeffects and enhanced axial resolution along a scan line. We describe a system in which a commercial ultrasound scanner was combined with a photorefractive crystal (PRC) based optical detection scheme to generate simultaneous 3D images of acoustic and optical properties of optically absorbing inclusions embedded in excised biological tissue. Representative images are presented that demonstrate the utility of this dual mode imaging technique. Technological limitations are discussed, as are plans for future work.